Efficacy and safety of Apixaban in the treatment of cerebral venous sinus thrombosis: a multi-center study - Simaan, Naaem; Metanis, Issa; Honig, Asaf; Hallevi, Hen; Filioglo, Andrei; Mendel, Rom; Barnea, Rani; Naftali, Jonathan; Auriel, Eitan; Aladdin, Shorooq; Orion, David; Dally, Najib; et al. (Frontiers in Neurology, 2024)
Background Information regarding the safety and efficacy of specific direct oral anticoagulants (DOAC) in the treatment of cerebral sinus and venous thrombosis (CSVT) is scarce. Apixaban is one of the most frequently prescribed DOACs. Therefore, we aimed to compare the safety and efficacy of Apixaban with those of vitamin k antagonists (VKA) in patients with CSVT. Methods Prospective CSVT databases from seven academic medical centers were retrospectively analyzed. Patients treated with Apixaban were compared to those treated with VKA. Data on demographics, clinical presentations, risk factors, radiological and outcome parameters were studied. Results Overall, 403 patients were included in the analysis. Of them, 48 (12%) were treated with Apixaban, and 355 (88%) were treated with VKA. Rates of coagulopathies were significantly higher in the VKA-treated patients but no other differences between the groups were found in baseline characteristics and underlying etiology. No significant differences were found between groups in efficacy or safety parameters including the rates of recanalization, favorable outcomes, one-year mortality, seizures, intracranial hemorrhage or CSVT recurrences. Conclusion Our data suggests that Apixaban may be safe and effective for patients with CSVT. These results should be tested in prospective randomized clinical studies.